Contribution of Micro Enterprises on Socio-Economic Aspects of Nepal - K.C. , Arjun (Rural Development Journal, 2019)
Microenterprise is defined as a small business engaged in the production of goods or services. Typically, microenterprises are characterized by their limited access to capital, minimal number of employees, and frequently operate from home. Micro-Enterprise is a small-scale economic unit involved in producing and distributing goods and services at the household level. This paper of micro-enterprises in Nepal is about how we helped them to grow because of their need and how they contributed to the well being of the Nepalese society at large. Secondary data were used for the study. These businesses require little capital start-up with facilities fixed in the market lodging or mobile commercial places. The analysis is based on the effect on the supported micro- enterprises under the Micro Entrepreneurs Development Program (MEDEP). The family component along with the use of local resources, small scale, labor-intensive and low capital input operations and the widespread use of adapted technology and unskilled labor mark the sector. For this reason micro-enterprises are best suited for disadvantaged communities. They are important for reducing poverty and promoting social and economic development in both rural and urban areas for social and economic development of Nepal. Their roles are important because they have qualities like creating self-employment opportunities, providing jobs for the poor and women, utilizing local resources, and fulfilling the basic needs of the impoverished.